2017
DOI: 10.1007/s10055-017-0306-3
|View full text |Cite
|
Sign up to set email alerts
|

When brands come to life: experimental research on the vividness effect of Virtual Reality in transformational marketing communications

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(144 citation statements)
references
References 41 publications
4
122
3
2
Order By: Relevance
“…Research on the use of VR devices has been conducted in various fields such as tourism (Huang, Backman, Backman, & Chang, ), education (Merchant, Goetz, Cifuentes, Keeney‐Kennicutt, & Davis, ), advertising (Van Kerrebroeck, Brengman, & Willems, ), and communication (Hammick & Lee, ), but no academic studies have been conducted in the field of nonprofit fundraising. VR is ripe for investigation as a fundraising technique because it is moving beyond the stage of experimentation to the stage of marketization in the media market.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the use of VR devices has been conducted in various fields such as tourism (Huang, Backman, Backman, & Chang, ), education (Merchant, Goetz, Cifuentes, Keeney‐Kennicutt, & Davis, ), advertising (Van Kerrebroeck, Brengman, & Willems, ), and communication (Hammick & Lee, ), but no academic studies have been conducted in the field of nonprofit fundraising. VR is ripe for investigation as a fundraising technique because it is moving beyond the stage of experimentation to the stage of marketization in the media market.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to emotional, i.e. hedonic benefits associated with products or brands literature is almost non-existent, with a notable exception of a study by Van Kerrebroeck et al (2017b). These authors found that VR generates higher perceptions of vividness and presence compared to a regular, two-dimensional video (Van Kerrebroeck et al, 2017b).…”
Section: Virtual Reality In Marketing Communicationmentioning
confidence: 97%
“…Chieng (2014) suggest that imagery richness can be affected by sound or animations. Various studies in marketing literature demonstrate that more vivid imagery results in more positive attitudes among consumers (Van Kerrebroeck et al, 2017b). Existing studies point consistently to the benefits of application of VR technology to informational marketing communications -that is, to presentation of functional, objective product attributes (Choi and Taylor, 2014).…”
Section: Virtual Reality In Marketing Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, new opportunities to creatively apply experimental approaches to study innovation management topics are rapidly emerging. In the domains of organizational behavior and marketing, scholars (e.g., Pierce and Aguinis, 1997; Van Kerrebroeck et al, 2017) have started applying virtual and augmented reality to conduct novel experimental research. This kind of emerging technology can represent opportunities for conducting alternative experiments on innovation topics.…”
Section: Deductive Quantitative Research On Innovation Managementmentioning
confidence: 99%